OPTIMALISASI PEMBELAJARAN JARAK JAUH DENGAN MEMANFAATKAN SARANA TEKNOLOGI INFORMASI DAN KOMUNIKASI (JS (JURNAL SEKOLAH), 2022)
Abstract: This research has a problem formulation, namely how to optimize distance learning with information and communication technology. The purpose of this research is to find out how the process of optimizing distance learning with information and communication technology. This research uses an approach approach, descriptive method. Qualitative research is presented descriptively. The subjects of this study were class III B teachers and class III B students at SDN Cikokol 1 Tangerang City. The object of this research is the process of optimizing distance learning with information and communication technology. Data collection techniques using interview and observation techniques. The results of this study indicate that in the distance learning process students are enthusiastic about participating in the learning process using information and communication technology. This can be seen from their activeness when carrying out distance learning. Students are also easier to catch and understand the subject matter so that students are more interested and more focused in learning. To optimize information and communication technology in distance learning is not yet fully optimal, because of this distance learning process, it becomes difficult for teachers to measure the level of student understanding, student character and assessment during their academic years. Even safe, this distance learning process is only 80% of students who can access the video conferencing used.Keywords: Optimal, Distance Learning, Technology, Information, Communication Abstrak: Penelitian ini memiliki rumusan masalah yaitu bagaimana mengoptimalisasi pembelajaran jarak jauh dengan teknologi informasi dan komunikasi. Tujuan dari penelitian ini adalah untuk mengetahui bagaimana proses mengoptimalisasi pembelajaran jarak jauh dengan teknologi informasi dan komunikasi.  Penelitian ini menggunakan pendekatan kualitatif, metode deskriptif. Penelitian kualitatif disajikan dengan deskriptif. Subjek penelitian ini adalah guru kelas III B dan siswa kelas III B SDN Cikokol 1 Kota Tangerang. Objek penelitian ini adalah proses optimalisasi pembelajaran jarak jauh dengan teknologi informasi dan komunikasi. Teknik pengumpulan data dengan menggunakan teknik wawancara dan observasi.  Hasil penelitian ini menunjukkan bahwa dalam proses pembelajaran jarak jauh  siswa sudah antusias selama mengikuti proses pembelajaran dengan menggunakan teknologi informasi dan komunikasi.Hal ini terlihat dari keaktifan mereka ketika sedang melaksanakan pembelajaran jarak jauh. Siswa juga lebih mudah menangkap dan memahami materi pelajaran sehingga siswa lebih tertarik dan lebih fokus dalam pembelajaran tersebut. Untuk optimalisasi teknologi informasi dan komunikasi dalam pembelajaran jarak jauh belum sepenuhnya optimal, karena selama proses pembelajaran jarak jauh ini, guru jadi sulit mengukur tingkat kepahaman siswa, karakter siswa dan penilaian akademiknya. Bahkan selama proses pembelajaran jarak jauh ini baru  80%  siswa yang bisa mengakses video conference yang digunakan. Kata Kunci: Optimal, Pembelajaran Jarak Jauh, Teknologi, Informasi, Komunikasi